Functional characterization of novel rare CYP2A6 variants and potential implications for clinical outcomes. Issue 1 (25th September 2021) - El‐Boraie, Ahmed; Tanner, Julie‐Anne; Zhu, Andy Z.X.; Claw, Katrina G.; Prasad, Bhagwat; Schuetz, Erin G.; Thummel, Kenneth E.; Fukunaga, Koya; Mushiroda, Taisei; Kubo, Michiaki; Benowitz, Neal L.; Lerman, Caryn; et al.
Abstract: CYP2A6 activity, phenotyped by the nicotine metabolite ratio (NMR), is a predictor of several smoking behaviors, including cessation and smoking‐related disease risk. The heritability of the NMR is 60–80%, yet weighted genetic risk scores (wGRSs) based on common variants explain only 30–35%. Rare variants (minor allele frequency <1%) are hypothesized to explain some of this missing heritability. We present two targeted sequencing studies where rare protein‐coding variants are functionally characterized in vivo, in silico, and in vitro to examine this hypothesis. In a smoking cessation trial, 1687 individuals were sequenced; characterization measures included the in vivo NMR, in vitro protein expression, and metabolic activity measured from recombinant proteins. In a human liver bank, 312 human liver samples were sequenced; measures included RNA expression, protein expression, and metabolic activity from extracted liver tissue. In total, 38 of 47 rare coding variants identified were novel; characterizations ranged from gain‐of‐function to loss‐of‐function. On a population level, the portion of NMR variation explained by the rare coding variants was small (~1%). However, upon incorporation, the accuracy of the wGRS was improved for individuals with rare protein‐coding variants (i.e., the residuals were reduced), and approximately one‐third of these individuals (12/39) were re‐assigned from normal to slow metabolizer status. Rare coding variants can alter an individual's CYP2A6 activity; their integration into wGRSs through precise functional characterization is necessary to accurately assess clinical outcomes and achieve precision medicine for all. Investigation into noncoding variants is warranted to further explain the missing heritability in the NMR.